Aplicação de técnica de laminação com acetato de celulose: estudo de caso em manuscritos iluminados de Minas Gerais - Patrícia Vaz de Mello Lavall (2021)
This research presents a material analysis of thirteen manuscript codices laminated with cellulose acetate belonging to the Ecclesiastical Archive of the Archdiocese of Mariana (AEAM). To understand how the development of lamination as a practice of support reinforcement took place, it was necessary to develop a brief historical survey of the paths taken by the nineteenth-century artisan-restorer, the technical-restorer and the twentieth-century conservator-restorer, in a process of cultural construction that started from a shift in the concepts of cultural heritage, consequences of wars, and the interference of science development. The events that led to the formation of the discipline of Paper Conservation are also presented. A survey was carried out on lamination techniques that were developed and recognized as an acceptable practice for preserving graphic documents over the decades, reflecting on the technologies created and disseminated as innovation in the preservation of collections. Finally, we will present the damage caused by the technique of lamination in the manuscripts included in this research. This work aims to carry out an investigative and comparative analysis that aims to compare information on damages raised by the bibliography, such as those found in the thirteen manuscripts, reflecting on how the choice for a certain restoration process can influence the appropriate and complete apprehension of a document, preventing observation of paints, techniques, textures and various other material evidences.